The growth of the services sector in the ECCU economies : implications for financing - Adrien, Peter ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Seeks to find out whether there is evidence to suggest that the services sector is the driver of the ECCU economy, as well as whether there is an under-supply of credit to services segments with high potential to growth.